Performance of an Alternative Generator Powered by Battery and Flywheel For Light Fishing Boats 3 Gt Fishermen Krueng Aceh - Juliardi, Juliardi; Maimun, Maimun; Dahlan, Dahmir; Darmawan, Darmawan; Barokah, Barokah; Himam, M.Iqbal (JURNAL BLUEFIN FISHERIES, 2022)
In the midst of the issue of limited natural resources, technological developments and industry, fishermen, especially Krueng Aceh fishermen who use the light fishing system at night to catch fish, have problems because they still use fuel to operate a portable electric generator.Researchers will conduct applied research on alternative electric generators using batteries and utilizing the Flywheel effect, with 48 Volt battery power, against a 36 volt BLDC electric motor and a capacity of 350 watts. This energy source from the battery will be used as the main source.The purpose of this research is to test the performance of an alternative electric generator powered by battery and flywheel without load and using a load (100,200 and 300 Watt AC electric lamps). The method that will be used is a direct test experiment with a light fishing system on a 3 GT fishing vessel Krueng Aceh.The results obtained from testing the performance of a generator without a load using a 37 kg flywheel, 42 cm diameter, 5 cm thick, and a battery voltage of 48 volts with a capacity of 20 Ah, capable of producing an AC output current with a voltage of 220 volts, 1500 RPM rotation, a frequency of 50 Hz. no burden. For testing with a light bulb load of 100 watts, the alternator RPM is 1500, the voltage is 210 Volts. As for the 200 watt load, the 1400 RPM voltage drops to 200 and the 300 Watt load RPM alternator 1200, the voltage is 110 volts.Keywords: Alternator, Battery, Battery Case, Electric Motor Flywheel.